SMARCA4: Current status and future perspectives in non-small-cell lung cancer. (1st February 2023) - Tian, Yumeng; Xu, Lu; Li, Xin; Li, Heming; Zhao, Mingfang
Abstract: SMARCA4, also known as transcription activator, is an ATP-dependent catalytic subunit of SWI/SNF (SWItch/Sucrose NonFermentable) chromatin-remodeling complexes that participates in the regulation of chromatin structure and gene expression by supplying energy. As a tumor suppressor that has aberrant expression in ∼10% of non-small-cell lung cancers (NSCLCs), SMARCA4 possesses many biological functions, including regulating gene expression, differentiation and transcription. Furthermore, NSCLC patients with SMARCA4 alterations have a weak response to conventional chemotherapy and poor prognosis. Therefore, the mechanisms of SMARCA4 in NSCLC development urgently need to be explored to identify novel biomarkers and precise therapeutic strategies for this subtype. This review systematically describes the biological functions of SMARCA4 and its role in NSCLC development, metastasis, functional epigenetics and potential therapeutic approaches for NSCLCs with SMARCA4 alterations. Additionally, this paper explores the relationship and regulatory mechanisms shared by SMARCA4 and its mutually exclusive catalytic subunit SMARCA2 . We aim to provide innovative treatment strategies and improve clinical outcomes for NSCLC patients with SMARCA4 alterations. Highlights: NSCLC patients with SMARCA4 alterations have a weak response to conventional chemotherapy and poor prognosis. CDK4/6 inhibitors, the small-molecule OXPHOS inhibitor and ATR inhibitors offer hope for SMARCA4 abnormalities patients. Cisplatin-based chemotherapy in combination with ICI therapy may be beneficial for SMARCA4- deficient NSCLC patients. As a key synthetic lethal target in SMARCA4 -deficient cancers, SMARCA2 may serve as a novel therapeutic target.